Mobilidade urbana sustentável e inclusiva : proposta de implantação de VLT (Veículo Leve sobre Trilhos) - Bernardes, Flaviane Fernandes (2016)
The search for the promotion of quality of life in cities stands out among one of the major contemporary challenges. The Sustainable Urban Mobility and outline alternatives for the improvement of Public Transport is fundamental to promote a more equitable, democratic and sustainable society. The Sustainable Urban Mobility is an integrated, comprehensive strategic thinking able to understand the numerous variables that make up the urban mobility of an economic factors, social, political and urban morphology. The studies focused on the adoption of innovative strategies to overcome the problems of urban public transport have contributed to resolving social demands. In order to meet the premises of Sustainable Urban Mobility for medium-sized cities, the public transport model, called VLT (Light Rail Vehicle), it is being as an alternative deployment models of public transport for some Brazilian cities. The VLT is a mode of public transport on rails, with some similar characteristics to the surface subway, having to ease their integration into the existing road structure. As a case study, we analyzed the Preliminary Technical Feasibility Study for Vehicle Deployment Light Rail in Uberlândia. Therefore, this study aims to analyze the characteristics of the urban transport model, VLT in order to investigate the conditions that have to improve urban mobility in cities, based on the principles of quality, sustainability and cost for socioeconomic development. The methodology for this study was based on the extensive literature present throughout the work, as well as the multi-criteria analysis, which uses criteria and attributes for a comparative study between two modes of present transport in the city of Uberlândia, BRT and LRT . The VLT\'s deployment proposed in Uberlândia-MG aims to integrate, extend and ensure the best operating level of comfort, safety, social inclusion and sustainability. They were defined two lines of VLT\'s (Purple Line and Green Line) proposed project, with a daily capacity of 80,000 passengers, containing 42 loading and unloading stations (with open fare integration) and length of 24 km in the urban fabric of the city, set in current integration system (SIT - Integrated Transport). Think of solutions to improve the Sustainable Public Transport is to contribute to the inclusion of different social classes in the system, through fairer prices and reduce environmental impacts in urban areas.